Capacidade funcional como fator preditivo de sobrevivência em idosos - Antoniucci, Juliana Marinho [UNESP] (Universidade Estadual Paulista (Unesp), 2013)
The aging process brings morphofunctional changes in all organ systems, hence there is a decrease in functional ability in older ages of life, and this relates to the survival of this population. In public health, functional capacity emerges as a new concept of health, better suited to implement and perform the health care of the elderly. Objective: To investigate the association between functional capacity, socio demographic factors and chronic diseases, also studying the survival of a population of elderly residents in Botucatu in the State of São Paulo (Brazil). Conducted analysis of baseline data from a cohort study initiated in 2003 in Botucatu - SP. Worked with a stratified sample of the population, randomly allocated from the Master Update 2000 Census and consists of 364 individuals 60 years and over for unknown prevalence. This study characterized the individuals with respect to sociodemographic characteristics, quality and lifestyle, physical activity, emotional state and morbidity. He returned to the field in 2006, when it was proposed multifunctional evaluation of these same seniors, with replacement of losses (deaths and refusals). We applied this return to the field scales Activities of Daily Living (ADLs) of Katz; Instrumental Activities of Daily Living (IADL) Lawton; Geriatric Depression Brief, Mini Mental State Examination - MMSE and Assessment of Alcohol-CAGE. In 2010 was held still new return to the field aiming to study the survival of this population in relation to functional capacity in these three years. We found that the prevalence of functional dependence of this population in 2006 was 5.7% to 14% for BADL's e IADL's. We found that the cognitive impairment was associated with age dependency and that after three years the survival curves were different when compared to populations with and without functional deficit for BADL and IADL. The impairment of functional capacity in the elderly can be considered a ...

O processo de envelhecimento acarreta modificações morfofuncionais em todos os sistemas orgânicos, consequentemente observa-se uma diminuição da capacidade funcional nas faixas etárias mais avançadas da vida, estando esta relacionada à sobrevivência desta população. Em saúde pública, a capacidade funcional surge como um novo conceito de saúde, mais adequado para instrumentalizar e operacionalizar a atenção à saúde do idoso. Verificar a associação entre a capacidade funcional, fatores sócio demográficos e doenças crônicas; também estudar a sobrevivência de uma população de idosos residentes no município de Botucatu no interior do Estado de São Paulo (Brasil). Realizado análise dos dados da linha de base de um estudo de coorte iniciado em 2003 no Município de Botucatu - SP. Trabalhou-se com uma amostra estratificada da população, alocada aleatoriamente à partir do Cadastro de Atualização do Censo de 2000 e constituída por 364 indivíduos de 60 anos e mais para prevalência desconhecida. Tal estudo caracterizou os indivíduos com relação aos aspectos sociodemográficos, qualidade e estilo de vida, atividade física, estado emocional e morbidade referida. Retornou-se ao campo em 2006, quando foi proposto avaliação multifuncional destes mesmos idosos, com reposição das perdas (mortes e recusas). Foram aplicados neste retorno ao campo as escalas de Atividades da Vida Diária (AVD) de Katz; Atividades Instrumentais de Vida Diária (AIVD) de Lawton; Depressão Geriátrica Abreviada, Mini Exame do Estado Mental - MEEM e Avaliação de Alcoolismo-CAGE. Em 2010 foi realizado ainda novo retorno ao campo objetivando estudar a sobrevivência desta população em relação à capacidade funcional nestes três anos. Constatamos que a prevalência de dependência funcional desta população estudada no ano de 2006 foi de 5,7% para ABVD´s e 14% para AIVD´s. Observamos que o déficit cognitivo se associou à ...
Keywords: Idosos; Envelhecimento; Aptidão fisica em idosos; Capacidade motora; Qualidade de vida; Saúde pública; Physical fitness for the aged; Botucatu (SP)